Clinical value of multidetector CT coronary angiography as a preoperative screening test before non-coronary cardiac surgery. Issue 12 (12th December 2006) - Russo, V; Gostoli, V; Lovato, L; Montalti, M; Marzocchi, A; Gavelli, G; Branzi, A; Di Bartolomeo, R; Fattori, R
Abstract : Objective: Myocardial scintigraphy and/or conventional angiography (CA) are often performed before cardiac surgery in an attempt to identify unsuspected coronary artery disease which might result in significant cardiac morbidity and mortality. Multidetector CT coronary angiography (MDCTCA) has a recognised high negative predictive value and may provide a non-invasive alternative in this subset of patients. The aim of this study was to evaluate the clinical value of MDCTCA as a preoperative screening test in candidates for non-coronary cardiac surgery. Methods: 132 patients underwent MDCTCA (Somatom Sensation 16 Cardiac, Siemens) in the assessment of the cardiac risk profile before surgery. Coronary arteries were screened for ⩾50% stenosis. Patients without significant stenosis (Group 1) underwent surgery without any adjunctive screening tests while all patients with coronary lesions ⩾50% at MDCTCA (Group 2) underwent CA. Results: 16 patients (12.1%) were excluded due to poor image quality. 72 patients without significant coronary stenosis at MDCTCA were submitted to surgery. 30 out of 36 patients with significant (⩾50%) coronary stenosis at MDCTCA and CA underwent adjunctive bypass surgery or coronary angioplasty. In 8 patients, MDCTCA overestimated the severity of the coronary lesions (>50% MDCTCA, <50% CA). No severe cardiovascular perioperative events such as myocardial ischaemia, myocardial infarction or cardiac failure occurred in any patient in Group 1. Conclusions: MDCTCA seems to be effective as a preoperative screening test prior to non-coronary cardiac surgery. In this era of cost containment and optimal care of patients, MDCTCA is able to provide coronary vessel and ventricular function evaluation and may become the method of choice for the assessment of a cardiovascular risk profile prior to major surgery.